2008
DOI: 10.1016/j.jvs.2008.03.043
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of visceral artery aneurysms: A 25-year experience

Abstract: In the era of minimally invasive therapeutic approaches, elective open surgical treatment of visceral artery aneurysms is safe and effective, and offers satisfactory early and long-term results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
233
0
13

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 311 publications
(249 citation statements)
references
References 34 publications
3
233
0
13
Order By: Relevance
“…It shows extended loss of arterial perfusion in the parenchyma distal to the coiled artery consistent with partial splenic infarction. or only partial primary success of 12.5 % in this study are not significantly greater than the results of other studies with re-intervention rates of 3 -11 % [12 -14] and comparable results of surgical therapy with re-operation rates of 0 -12 % [13,15,16]. The mortality rate of the elective surgical therapy of visceral aneurysms is approximately 5 % [15,17].…”
Section: Discussionsupporting
confidence: 41%
“…It shows extended loss of arterial perfusion in the parenchyma distal to the coiled artery consistent with partial splenic infarction. or only partial primary success of 12.5 % in this study are not significantly greater than the results of other studies with re-intervention rates of 3 -11 % [12 -14] and comparable results of surgical therapy with re-operation rates of 0 -12 % [13,15,16]. The mortality rate of the elective surgical therapy of visceral aneurysms is approximately 5 % [15,17].…”
Section: Discussionsupporting
confidence: 41%
“…6 In a study conducted by Pulli et al, only one out of 55 patients showed right gastroepiploic aneurysm, and this case was diagnosed incidentally during abdominal ultrasound. 7 As in the case presented here, right gastroepiploic artery aneurysm is among the rarest forms.…”
Section: Discussionmentioning
confidence: 53%
“…3,4 Although a laparoscopic approach is reported to be feasible, especially for splenic artery aneurysm, 2,16,17 the incision to extract the specimen is essential. In this case, the aneurysm was 4.5 cm in diameter, and intracorporeal mobilization was unnecessary because the lesion was located in the distal part of the SMA.…”
Section: Discussionmentioning
confidence: 99%